Empowerment Model as a Form of Pesantren Economic Welfare with a Triple Bottom Line Approach A Case Study of Pondok Pesantren Karangasem Muhammadiyah Paciran - Firmansyah, Bayu (Universitas Siliwangi, 2025)
Introduction to The Problem: This research examines the economic empowerment model applied at Pondok Pesantren Karangasem Muhammadiyah Paciran, focusing on evaluating holistic sustainability through the triple bottom ine (TBL) framework. TBL is an approach that assesses an organization's performance not only from a financial aspect (profit) but also from its social (people) and environmental (planet) impact.Purpose/Objective Study: The main objective of this study is to analyze the extent to which the pesantren's empowerment model is able to integrate these three pillars to create sustainable welfare.Design/Methodology/Approach: Using a qualitative methodology, data were collected through in-depth interviews, direct observation, and documentation studies.Findings: The research findings indicate that Pondok Pesantren Karangasem has successfully implemented two main TBL pillars very well, namely profit and people. The profits generated from various business units such as plantations and livestock are effectively used to finance pesantren operations and provide scholarships for underprivileged students, demonstrating success from the financial side. Furthermore, the people dimension is realized through the creation of job opportunities for the surrounding community, skills training programs, and the provision of affordable healthcare and educational services, which significantly improve community welfare. However, the research findings also reveal that the commitment to the planet or environmental pillar has not yet been optimally implemented. Waste management from livestock business units and the use of natural resources still do not adhere to environmentally friendly sustainable practicesPaper Type: Research Article